Improvement of Populus deltoides Bartr. Ex Marsh. in India - I. Present Status - Kumar, Dinesh; Singh, N. B.; Rawat, G. S.; Srivastava , Shivendu (Indian Forester, 1999)
Progress made in India about introduction and further improvement of P. deltoides is reviewed. Out of the hundreds of clones of P. deltoides introduced in India over the past four decades, only 3 to 4 clones (out of which 2 to 3 originated from the same geographical area) are widely grown by farmers in their agroforestry plantations in the plains of western Uttar Pradesh, Haryana and Punjab. In order to undertake multilocation trials ofa greater number of promising clones, 108 clones have been ranked on the basis of their field performance in two trials. Several clones rank higher than G-3 (which is presently one of the most popular clones of this species in India) and they need to be tested in field trials at multiple sites allover the poplar-growing region of the country. Germplasm of P. deltoides presently available in India comes from only about 25 per cent of the native range of this species in the U.S.A. Introduction of more germplasm from wild stands in the U.S.A is suggested. Some clones from open-pollinated progeny of G-48 and G-3 have been developed in the past few years, but open-pollinated progeny cannot be used in long-term breeding programme. Need to start control-pollination work using appropriate mating design has also been emphasised. This review has provided the basis for development of an All-India Coordinated Project for Improvement of Poplar to be executed by Forest Research Institute, Dehra Dun in collaboration with the research units of State Forest Departments and universities.